2004
DOI: 10.4141/a03-046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partially replacing silage with straw-barleysoybean meal mixtures on cow-calf performance

Abstract: Charmley, E. and Duynisveld, J. L. 2004. Effect of partially replacing silage with straw-barley-soybean meal mixtures on cow-calf performance. Can. J. Anim. Sci. 84: 237-244. Forty-eight multiparous, medium-framed cows, calving between Jan. 02 and Mar. 05 were used in a 3 × 2 factorial experiment with three totally mixed ration (TMR) formulations and two levels of protein supplementation. The TMRs were formulated to contain 75, 50 or 25% silage (DM basis). The balance of the diet comprised barley, barley straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, in contrast to energy, beef cows often exhibit a response in milk production and calf performance when diets are supplemented with protein. This is most apparent in low protein diets (de Garcia and Ward 1991;Wiley et al 1991;Dhuyvetter et al 1993), but has also been observed in diets of higher protein concentration, where the protein is highly degradable in the rumen (Rusche et al 1993;Charmley et al 1999;Charmley and Duynisveld 2004).…”
mentioning
confidence: 92%
“…However, in contrast to energy, beef cows often exhibit a response in milk production and calf performance when diets are supplemented with protein. This is most apparent in low protein diets (de Garcia and Ward 1991;Wiley et al 1991;Dhuyvetter et al 1993), but has also been observed in diets of higher protein concentration, where the protein is highly degradable in the rumen (Rusche et al 1993;Charmley et al 1999;Charmley and Duynisveld 2004).…”
mentioning
confidence: 92%